Correlation Between the Number of Lenticulostriate Arteries and Imaging of Cerebral Small Vessel Disease - Chen, Yuan-Chang; Wei, Xiao-Er; Lu, Jing; Qiao, Rui-Hua; Shen, Xue-Feng; Li, Yue-Hua (Frontiers in Neurology, 2019)
Background and purpose: Hypoperfusion plays an important role in the pathophysiology of cerebral small vessel disease (SVD). Lenticulostriate arteries (LSAs) are some of the most important cerebral arterial small vessels. This study aimed to investigate whether the number of LSAs was associated with the cerebral perfusion in SVD patients and determine the correlation between the number of LSAs and SVD severity. Methods: Five hundred and ninety-four consecutive patients who underwent digital subtraction angiography were enrolled in this study. The number of LSAs was determined. Computed tomography perfusion (CTP) was used to calculate the cerebral blood flow (CBF), cerebral blood volume (CBV), mean transit time (MTT) and time to peak (TTP). Magnetic resonance imaging (MRI) was performed to assess cerebral infarct, cerebral microbleeds (CMBs), white matter hyperintensities (WMHs), enlarged perivascular spaces (EPVSs), and lacunes. An SVD compound score was calculated to express the level of cerebral SVD load. Results: The SVD scores were negatively correlated with the number of the LSAs (P <0.001, rs=-0.44). The number of LSAs was inversely associated with the presence of any type of SVD (P <0.001). The adjusted ORs of the SVD severity were 0.31 for LSA group 1 (LSA >20) vs. group 2 (LSA=10-20) and 0.47 for LSA group 2 (LSA=10-20) vs. group 3 (LSA <10). MTT and TTP were significantly higher and CBF was significantly lower when the number of LSAs was between 5 and 10 on each side of the basal ganglia (P <0.001, <0.001 and <0.001, respectively). The CBV was slightly lower when the number of LSAs was between 5 and 10, while it was significantly lower when the number was less than 5 on each side of the basal ganglia (P <0.05, <0.0001, respectively). Conclusion: LSA count was lower in SVD patients than the non-SVD participants and there was a positive correlation between the cerebral perfusion and the number of LSAs. The LSA number was negatively associated with SVD severity, hypoperfusion might play an important role. This finding may have potentially important clinical implications for monitoring LSA in SVD patients.